Housing, dynamics of regional labour markets and migration - Petri Böckerman; Kari Hämäläinen (European Regional Science Association (ERSA), 2002)
The aim of this study is to explore the structure and the dynamics of regional labour markets in terms of gross migration flows in Finland. The study addresses also the composition of gross migration flows. The study exploits the fact that Finland is divided into 85 sub-regions (the so-called NUTS4-level in the European Union). The yearly observations cover the period from 1989 to 1997. Gross migration rates are related to macroeconomic indicators, demographic factors, industry-structure and gross flows of jobs and workers by employing the data of 85 Finnish regions. The variables that characterize the evolution of gross migration flows and the structure of economic fundamentals in the Finnish regions are collected by using aggregate data from Statistics Finland. The study includes macroeconomic indicators due to the fluctuations of the Finnish economy over the period of the investigation. The measurement of regional labour market flows applies a large longitudinal data of employees over the period from 1987 to 1997. The applied panel data is constructed by matching the measures of gross and worker flows and gross migration flows with the economic fundamentals (including macroeconomic indicators). The estimation results imply that different factors can have similar effects on net changes in migration flows by various means of affecting gross changes. In particular, the migration equations show that the idiosyncratic factors (i.e. unobservable individual-level characteristics) play definitely a more important role for gross migration flows of employees with higher university degrees.
Keywords: 330